تعمیرِ شخصیت میں عبادات کا کردار: ارکانِ اسلام کا مطالعہAll world religions emphasize worship, but in Islam worship has a special place. Worship in Islam means obedience of Allah at every step of life. This article studies the role of worship in character building and personality development with special focus on the pillars of Islam: Namāz, Roza, Zakāt and Ḥajj. It finds that these pillars greatly affect human life. It strengthens the relationship between Allah and man. It urges man to care for the rights of others. When we take care of the rights of others, society becomes an example of paradise.: Role of Ibādāt in Personality Development: A Study of the Pillars of Islam (Al-Qamar, 2019)
All world religions emphasize worship, but in Islam worship has a special place. Worship in Islam means obedience of Allah at every step of life. This article studies the role of worship in character building and personality development with special focus on the pillars of Islam: Namāz, Roza, Zakāt and Ḥajj. It finds that these pillars greatly affect human life. It strengthens the relationship between Allah and man. It urges man to care for the rights of others. When we take care of the rights of others, society becomes an example of paradise.
Keywords: The Government Sadiq College Women University Bahawalpur